Detrimental Effects of Neem Seed on Different Life Stages of Red Flour Beetle, Tribolium castaneum - Syeda Azra Tariq; Muhammad Farhanullah Khan; Habibullah Rana (Journal of Basic & Applied Sciences, 2013)
Fine Neem Seed Powder (NSP) was tested in three dozes, viz. 0.5%, 1.0% and 2.0% (w/w) for determination of its toxicity and detrimental effects on life stages of red flour beetle, Tribolium castaneum. Fifty gram treated and untreated (control) wheat was kept in glass jars and 10 pairs of the beetles were released in each. Mortality count was made after 72 hours. LD50 calculated as 1.841% NSP in wheat (w/w). NSP served as an Insect Growth Regulator (IGR). It was observed that at 0.5% dose, the number of larvae was not very different to control but the weight of larvae was lesser. At 1.0% dose, the number and weight of larvae were significantly reduced. At 2.0% dose, both the number and weight of larvae, pupae and adults were reduced remarkably. The insect growth inhibition was increased by increasing the dose of NSP.